2002
DOI: 10.1161/01.cir.0000014686.73212.da
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Matrix Metalloproteinase Inhibition on Ventricular Remodeling Due to Volume Overload

Abstract: Background-Left ventricular (LV) hypertrophy and dilatation are important compensatory responses to chronic volume overload. Although LV function is initially preserved by these responses, the continued structural remodeling of the myocardium ultimately becomes maladaptive, leading to the development of heart failure. We have shown previously that increased myocardial matrix metalloproteinase (MMP) activity precedes LV dilatation induced by a chronic volume overload. Accordingly, this study focused on the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
103
1
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(121 citation statements)
references
References 38 publications
11
103
1
2
Order By: Relevance
“…Mast cell-mediated MMP activation, leading to degradation of the extracellular matrix and ventricular dilatation, are well-documented features in this model of heart failure (3,6,8,9,20). The stimulus initiating this mast cell-mediated remodeling is unknown; however, we recently demonstrated that ET-1 is capable of causing cardiac mast cell degranulation and the subsequent activation of MMPs ex vivo (31).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Mast cell-mediated MMP activation, leading to degradation of the extracellular matrix and ventricular dilatation, are well-documented features in this model of heart failure (3,6,8,9,20). The stimulus initiating this mast cell-mediated remodeling is unknown; however, we recently demonstrated that ET-1 is capable of causing cardiac mast cell degranulation and the subsequent activation of MMPs ex vivo (31).…”
Section: Discussionmentioning
confidence: 82%
“…Previous studies from our laboratory using the aortocaval (AV) fistula model of volume overload established a causal role for cardiac mast cells in the activation of matrix metalloproteinases (MMPs) (3,8,22,31). The role of MMPs in mediating the degradation of the extracellular matrix leading to ventricular dilatation has been well documented (3,6,9,20,38). However, the potential for ET-1 to directly impact myocardial remodeling was recently established by our study, demonstrating that ET-1 causes degranulation of resident cardiac mast cells (31).…”
mentioning
confidence: 99%
“…In the setting of pure volume overload through the creation of arteriovenous fistula, Chancey et al (19) have confirmed that the administration of an MMP inhibitor can effectively decrease cardiac dilation, reduce wall stress and left ventricular hypertrophy, and preserve ventricular function.…”
Section: Mmps In Cardiovascular Diseasementioning
confidence: 98%
“…In contrast to the marked accentuation in collagen deposition triggered by a pressure load, volume overload is associated with a reduction in interstitial collagen content due to increased MMP expression (113)(114)(115) and augmented autophagic degradation of procollagen in cardiac fibroblasts (116). Pharmacologic inhibition studies suggested that MMP activation is directly implicated in dilative remodeling of the volume-overloaded ventricle (117), but the mechanisms responsible for the distinct cell biological changes and matrix alterations in volume overload remain poorly understood. Bradykinin receptor signaling has been implicated in matrix loss associated with volume overload (118), but the links between specific mechanical stimuli and myocardial cell activation are understudied.…”
Section: Ecm In Cardiac Pressure and Volume Overloadmentioning
confidence: 99%